Effects of atom- and phase-scale compressive stress on fracture toughness in yttrium-doped lanthanum zirconate solid solutions. Issue 6 (15th April 2018) - Wang, Yanfei; Xiao, Ping; Yang, Huan; Wang, Siqing; Liu, Rongjun; Cao, Yingbin
Abstract: The poor fracture toughness of cubic pyrochlores has severely blocked their wide application. To toughen them, a series of yttrium dopants have been introduced to lanthanum zirconate, creating atomic or phase-scale compressive stress dependent on the concentration of dopants. We find bigger substitutional dopants, rather than smaller ones, can toughen cubic ceramics, attributing to the dominance of an imposed atomic compressive stress to surroundings over the local one near normal point defects. For special point defects such as oxygen vacancies or interstitials, the local stress in their vicinity could become dominant given an adequate concentration. Despite of the pyrochlore/fluorite intermixture possessing evidently reduced grains, it only exhibits intermediate fracture toughness, suggesting negligible grain refining effects on toughening. Further, a random distribution of atomic compressive stress induced by disordered oxygen vacancies is beneficial to toughening. This research highlights the atomic compressive stress on toughening, providing guidance for future design of novel thermal barrier coatings.